2019
DOI: 10.1093/annonc/mdz407
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib in c-MET- or ROS1-positive NSCLC: results of the AcSé phase II trial

Abstract: Background: In 2013, the French National Cancer Institute initiated the AcSé program to provide patients with secure access to targeted therapies outside of their marketed approvals. Efficacy and safety was then assessed using a two-stage Simon phase II trial design. When the study design was designed, crizotinib was approved only as monotherapy for adults with anaplastic lymphoma kinase plus non-small-cell lung cancers (NSCLC).Patients and methods: Advanced NSCLC patients with c-MET 6 copies, c-MET-mutated, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 19 publications
5
98
1
Order By: Relevance
“…[32][33][34] Updated results of the AcSé phase II trial showed a higher best ORR of 69.4% during treatment in 37 patients of an ROS1-translocation cohort. 35 Similarly, the METROS phase II trial also showed a very high ORR of 65% and median PFS of 22.8 (95% CI 15.2--30.3 months with crizotinib therapy among 26 patients with ROS1-rearranged pretreated NSCLC. 36 Two studies from India have reported a good response to crizotinib therapy.…”
Section: Discussionmentioning
confidence: 93%
“…[32][33][34] Updated results of the AcSé phase II trial showed a higher best ORR of 69.4% during treatment in 37 patients of an ROS1-translocation cohort. 35 Similarly, the METROS phase II trial also showed a very high ORR of 65% and median PFS of 22.8 (95% CI 15.2--30.3 months with crizotinib therapy among 26 patients with ROS1-rearranged pretreated NSCLC. 36 Two studies from India have reported a good response to crizotinib therapy.…”
Section: Discussionmentioning
confidence: 93%
“…6,21,22 The program accès sécurisé à des thérapies ciblées innovantes (AcSé) was established by the INCa to develop clinical trials with different targeted therapies for cancer patients showing specific genomic alterations, notably on MET, RET, HER2, or BRAF. [23][24][25][26] These genomic alterations could be investigated not only in advanced NSCLC, but also in a number of other solid tumors. The patients presenting a specific molecular alteration could be included in a clinical trial.…”
Section: Extension Of Gene Cancer Molecular Testing and Disseminationmentioning
confidence: 99%
“…87 The AcSé phase II trials on 25 crizotinib-treated patients with MET amplification (GCN>6), the ORR was 16%, and the respective median PFS and OS were 3.2 (95% CI: 1.9-3.7) months and 7.7 (95% CI: 4.6-15.7) months. 88 Tivantinib also yielded disappointing results for patients with MET amplification (defined as GCN>4): median PFS last 3.6 months for those given the erlotinib-tivantinib combination, as for those taking erlotinib alone. 83 Other molecules, like tepotinib or capmatinib, are being tested to treat this anomaly.…”
Section: Met-amplified Nsclcs De Novo Amplificationmentioning
confidence: 99%
“…No difference between MET-amplified and METex14-mutated patients was found for any clinical endpoint. 87 In the AcSé crizotinib study, 88 In light of the outcomes of the Profile-1001 study, in 2018, the FDA granted, crizotinib (Xalkori) a breakthroughtherapy designation for the treatment of patients with NSCLC harboring METex14 alterations that progressed after receiving platinum-based chemotherapy.…”
Section: Evaluation Of Anti-met Agents In Patients With Nsclcs Harbormentioning
confidence: 99%